Experts’ and Novices’ Perception of Ignorance and Knowledge in Different Research Disciplines and Its Relation to Belief in Certainty of Knowledge - Hansson, Isabelle; Buratti, Sandra; Allwood, Carl Martin (Frontiers in Psychology, 2017)
Assessments of the extent of knowledge in a domain can be important since non-identified lack of knowledge may lead to decisions that do not consider the effect of relevant factors. Two studies examined experts’ and novices’ perception of their own ignorance and knowledge out of everything there is to know within their own and other disciplines and their assessments of their, and other disciplines’ knowledge of all there is to know in each discipline. In total 380 experts and 401 students from the disciplines of history, medicine, physics, and psychology participated. The results for ignorance and knowledge assessments of one’s own knowledge were similar. Novices reported more ignorance and less knowledge in their own discipline than experts, but no differences were found in the assessments of how much is known in each discipline. General belief in certainty of knowledge was associated with the knowledge assessments and level of expertise. Finally, disciplinary differences were found both for the knowledge assessments and for belief in certainty of knowledge. Historians and physicists assessed that less was known in their own discipline out of all there is to know (approx. 40 %), compared to the medics (about 50 %). Historians believed least in certainty of knowledge and physicists most. Our results have practical implications for higher educational teaching and interdisciplinary collaboration.